Economics of Higher Education: Research Publications in English in Canada, 1971 to 1981 - Stager, David (Canadian Journal of Higher Education, 1982)
Research in the economics of education declined from the early 1970s to the end of the decade. American studies in the early 1960s had stimulated work on the contribution of education to economic growth and earnings differentials, but rapid expansion in post-secondary education led to declining relative earnings of graduates and a disillusionment with investment in higher education. In Canada, renegotiations of the Fiscal Arrangements Act in 1971-72 simply extended the 1967 provisions and dampened further interest in alternative financing arrange- ments. Topics researched in the 1970s in Canada were similar to those examined elsewhere: rates of return, institutional costs and efficiency, demand for educa- tion, income redistribution, alternative financing, manpower planning. Current work emphasizes enrolment flows. Future research should be directed to the demand for education and the relationship between education and earnings.